Application of 1-d analytical solution for salt intrusion investigation in the Kuantan estuary during low water - Tan, Wei Mong (2017)
The increase of sea level and extreme dry weather due to climate change has increased the estuary water salinity. As the consequences, the sea water intrudes further into the fresh water region. In March 2016, the residents in Kuantan claimed that the water supply was salty and this happened because the water intake station at Kobat was affected by saline water. Hence, the aims of this are to 1) investigate the salinity intrusion profile in Kuantan Estuary during low water; 2) to test the applicability of 1-D analytical solution for salt intrusion investigation in the Kuantan Estuary; and 3) to verify and validate the Van der Burgh’s coefficient. Data collection of salinity started from the mouth of Kuantan Estuary up to the Kobat Barrage covering a distance of 18.40km. During the spring tidal condition, the longitudinal salinity distribution has been successfully simulated using the 1-D salt intrusion model despite of several outliers caused by some geographical changes. From the results, it shows that the salinity distribution in the Kuantan Estuary has been largely disturbed with certain level of instability after the construction of the Barrage. The Van der Burgh’s coefficient K obtained from the calibration has the value of 0.40 and this coefficient has been validated from the 2nd survey.